2015
DOI: 10.1111/evo.12639
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying hummingbird preference for floral trait combinations: The role of selection on trait interactions in the evolution of pollination syndromes

Abstract: Darwin recognized the flower's importance for the study of adaptation and emphasized that the flower's functionality reflects the coordinated action of multiple traits. Here we use a multitrait manipulative approach to quantify the potential role of selection acting on floral trait combinations underlying the divergence and maintenance of three related North American species of Silene (Caryophyllaceae). We artificially generated 48 plant phenotypes corresponding to all combinations of key attractive traits dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 77 publications
(104 reference statements)
2
56
0
1
Order By: Relevance
“…Given evidence for reproductive Allee effects, competition for pollinators, and predispersal seed predation across S. angularis populations (Spigler & Chang, , ), we interpret our data to indicate that the negative effects of flowering synchronously begin to outweigh the benefits where pollen receipt is sufficient. For these and all fitness surfaces presented here, however, we caution that interpretations may be complicated by the influence of correlational selection among traits (Schluter & Nychka, ), which has been examined more intensively in other work (Reynolds et al ., ; Fenster et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Given evidence for reproductive Allee effects, competition for pollinators, and predispersal seed predation across S. angularis populations (Spigler & Chang, , ), we interpret our data to indicate that the negative effects of flowering synchronously begin to outweigh the benefits where pollen receipt is sufficient. For these and all fitness surfaces presented here, however, we caution that interpretations may be complicated by the influence of correlational selection among traits (Schluter & Nychka, ), which has been examined more intensively in other work (Reynolds et al ., ; Fenster et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…; Fenster et al . ). These insights would be not possible from simple species occurrence data or analysis of pairwise interactions.…”
Section: Introductionmentioning
confidence: 97%
“…Empirical evidence has shown that pollinators can impose selection pressure upon individual floral traits (Harder & Johnson, ), pairs of correlated traits (Campbell, ; Delph et al ., ; Benitez‐Vieyra et al ., , ; Baranzelli et al ., ; Fenster et al ., ) and higher interaction levels among traits like phenotypic integration (Ordano et al ., ). In addition, recent correlative evidence suggests that pollinator‐mediated selection can increase the floral integration (GonzĂĄlez et al ., ).…”
Section: Introductionmentioning
confidence: 99%